Strengthening Adaptive Governance to Optimize the Function of Green Open Spaces in Improving the Quality of Life in Urban Areas - Iin Endah Setyawati; Dina; Husni Farhani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Rapid urbanization has increased the quantity and quality of green open spaces (GOS) in urban areas, impacting the quality of life of residents. The purpose of this study is to evaluate the benefits of adaptive governance in optimizing the function of GOS. This is done by comparing policy implementation in several major cities in Indonesia. This study investigates GOS management practices in several cities—Surabaya, Bandung, and Semarang—which have different social, ecological, and institutional characteristics. This was done using a comparative case study approach. Data were collected through field observations, in-depth interviews with key stakeholders (local governments, community groups, and environmental NGOs), and analysis of policy documents and secondary data from 2015 to 2020. The research findings indicate that adaptive governance relies heavily on three key factors: (1) the level of multi-stakeholder participation in the planning and maintenance of green open spaces; (2) the flexibility of regional policies to adapt to changing community needs and environmental conditions; and (3) ongoing monitoring and evaluation mechanisms. Semarang demonstrates adaptation to environmental risks, Bandung develops a thematic public space policy, and Surabaya excels in integrating community participation. This study helps develop a comparative framework for adaptive green open space governance. This framework can be used by other regional governments to create more responsive, collaborative, and sustainable policies to improve the quality of life for urban communities in Indonesia.